2012
DOI: 10.1523/jneurosci.4731-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Plasticity of Hippocampal Adult-Born Neurons

Abstract: Adult neurogenesis occurs in the dentate gyrus of the hippocampus, which is a key structure in learning and memory. It is believed that adult-born neurons exert their unique role in information processing due to their high plasticity during immature stage that renders them malleable in response to environmental demands. Here, we demonstrate that, in rats, there is no critical time window for experience-induced dendritic plasticity of adult-born neurons as spatial learning in the water maze sculpts the dendriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 60 publications
5
115
3
2
Order By: Relevance
“…Indeed, by imaging new neurons using Zif268, it has been shown that spatial learning recruited 4-mo-old adult-born neurons (Tronel et al 2014). Depleting specifically these "old" adult-born neurons (by 1-wk AraC treatment 4 mo before training) delays learning (Lemaire et al 2012). These data indicating that adult-born neurons do not have a time-dependent role are consistent with the observation that they survive several months (Kempermann et al 2003).…”
Section: Immature Versus Mature Adult-born Neuronssupporting
confidence: 70%
See 4 more Smart Citations
“…Indeed, by imaging new neurons using Zif268, it has been shown that spatial learning recruited 4-mo-old adult-born neurons (Tronel et al 2014). Depleting specifically these "old" adult-born neurons (by 1-wk AraC treatment 4 mo before training) delays learning (Lemaire et al 2012). These data indicating that adult-born neurons do not have a time-dependent role are consistent with the observation that they survive several months (Kempermann et al 2003).…”
Section: Immature Versus Mature Adult-born Neuronssupporting
confidence: 70%
“…When testing spatial memory ability, deficits were described in some studies (Snyder et al 2005;Fan et al 2007;Dupret et al 2008;FarioliVecchioli et al 2008;Imayoshi et al 2008;Garthe et al 2009;Lemaire et al 2012), but not in others (Shors et al 2002;Madsen et al 2003;Raber et al 2004;Meshi et al 2006;Saxe et al 2006;Winocur et al 2006;Wojtowicz et al 2008). From our own study, based on a model that consisted in selectively ablating adult hippocampal neurogenesis by overexpressing the proapoptotic protein Bax in neuronal precursors on administration of doxycycline, we concluded that adult-born neurons are required for an allocentric (and not egocentric) strategy and for the flexible use of the acquired information (Dupret et al 2008).…”
Section: Causationmentioning
confidence: 62%
See 3 more Smart Citations